Answer:
s = - 1 ± ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Step-by-step explanation:
Given
s² + 2s - 6 = 0 ( add 6 to both sides )
s² + 2s = 6
To complete the square
add ( half the coefficient of the s- term )² to both sides
s² + 2(1)s + 1 = 6 + 1
(s + 1)² = 7 ( take the square root of both sides )
s + 1 = ±
( subtract 1 from both sides )
s = - 1 ± ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Thus
s = - 1 -
, s = - 1 + ![\sqrt{7}](https://tex.z-dn.net/?f=%5Csqrt%7B7%7D)
Answer:
the 2nd one
Step-by-step explanation:
Answer:
18y^3 + 24y^5.
Step-by-step explanation:
6y^3(3 + 4y^2)
= 6*3 y^3 + 6*4 y^(3+2)
= 18y^3 + 24y^5.
Answer:
i think
x=36 and y=13
Step-by-step explanation: